Perancangan Sistem Monitoring Pada Water Purifier Berbasis Website - Tito Chandra Dinata Arifin; Dean Corio; Afit Miranto (Politeknik Negeri Jakarta, 2022)
The need for drinking water is one of the basic needs that must be met by humans, drinking water has various kinds of compounds and bacteria in it. Drinking water is generally the result of processing with various methods, one of which is the use of nonthermal plasma technology. With the presence of non-thermal plasma technology to kill bacteria such as e-coli and other microorganisms with a working system that eliminates bacteria in the air. This looks effective when we use plasma because with high voltage the bacteria will die. In well water which is usually used for cooking and drinking in households, the bacteria or microorganisms in it are not completely killed. This water purification system is very useful if it is developed especially in areas that have not been reached by clean water or PDAM, in rural areas it is estimated to be very effective. This tool works well. Generally, in rural areas, the use of the latest technology is not too much. With the addition of a part of a microcontroller system and a monitoring system in the form of a website, it is very easy to operate this tool, we can combine the PH and TDS of the water we are going to purify. Equipped with a microcontroller system that makes it easy to control something and run tool commands. Keywords: Non-Thermal Plasma, PH, TDS, Microcontroller System, Monitoring System